IC 9131 Foreign Direct Investment In The U.S. Minerals Industry - Louis J. Sousa (The National Institute for Occupational Safety and Health (NIOSH), 1987)
This Bureau of Mines report examines aggregate trends in foreign direct investment in the U.S. mining and mineral processing industries between 1977 and 1984, and provides an analysis of foreign investment in several major mineral commodity industries. In 1984, 11.1 pct of total employment in the U.S. minerals industry was at firms that were U.S. affiliates of foreign firms. In 1985, the proportion of U.S. capacity held by foreign investors in nine major mineral commodity industries was as follows: steel, 5 pct; silver, 16 pct; lead, 18 pct; aluminum, 25 pct; zinc, 26 pct ; copper, 30 pet; cement, 32: pct; gold, 44 pct; and ferroalloys, 56 pct. Almost 90 pct of the total foreign investment in the U.S. minerals industry was accounted for by eight countries-Canada, the United Kingdom, France, Federal Republic of Germany, Switzerland, Japan, Australia, and the Republic of South Africa. The most fundamental reason behind the growth in foreign investment in the U.S. minerals industry has been that an increasing proportion of U.S. mineral firms and assets have been for safe, while foreign mineral companies have been the ones most willing and able to purchase these firms and/or their assets. mile the growth in foreign ownership in the minerals industry has not been without controversy, it has helped save jobs, reduce the minerals trade deficit, and- from the national defense perspective-maintain the Nation's overall mineral and metal self-sufficiency at reasonably high levels. In the absence of domestic buyers, foreign investors have helped to maintain a viable domestic minerals industry.